High-performance non-fullerene polymer solar cells based on naphthobistriazole wide bandgap donor copolymers. Issue 16 (29th March 2019) - Li, Li; Liu, Gongchu; Zhang, Jie; Wang, Zhenfeng; Jia, Tao; Hu, Yingyuan; Cao, Congcong; Zhang, Kai; Huang, Fei; Cao, Yong
Abstract : The non-fullerene polymer solar cells (NF-PSCs) devices based on thePFBTZNT :m-ITIC system exhibited a power conversion efficiency of up to 11.02%. Abstract : Two wide bandgap conjugated polymers (PBTZNT andPFBTZNT ) based on naphthobistriazole (TZNT) as the acceptor unit and benzodithiophene (BDT) as the donor unit were developed and applied in non-fullerene polymer solar cells (NF-PSCs). Detailed investigations revealed that the TZNT unit and fluorine atom substitution of BDT have significant influence on the resultants' optical and electronic properties, molecular aggregation properties, and charge separation in the bulk-heterojunction films, and thus the overall photovoltaic performances. Two copolymers exhibited wide optical bandgaps, strong absorption and high hole mobility. The NF-PSCs based on the resulting copolymers as the donor materials and m-ITIC as the electron acceptor exhibited impressive photovoltaic performances. Among them, the devices based on thePFBTZNT :m-ITIC system exhibited a high power conversion efficiency of up to 11.02%. This work demonstrates that the TZNT unit is a promising candidate as an electron-deficient building block for high performance NF-PSCs, and side-chain engineering with the addition of fluorine substituents is an effective molecular design strategy for further improvement of the photovoltaic performance.